1973
DOI: 10.1007/bf03158071
|View full text |Cite
|
Sign up to set email alerts
|

Average cross sections for Pu-α-Be neutrons: Low-energy neutrons from α-n sources

Abstract: Average activation cross sections for a number of elements were determined using unmoderated neutrons from Pu-Be and Po-Be sources. Applying threshold detectors it was found that 10% of Pu-Be neutrons are emitted in the energy interval 10--100 keV. Neutron spectra from Pu-Be13 sources of different dimensions were the same within the interval 0.5--5 Ci; the majority of neutrons below 2 MeV carne from the multibody break-up of 13C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…According to the data obtained from Figures 8 and 9, it was observed that at a low energy range of 1.5 to 2.5 Mev, there is an evident increase in the flux intensity of fast neutrons at all spectra for all samples. These high neutron fluxes emanated from the fission of plutonium and the (n, 2n) reaction with Be nuclei are more significant due to the large size of the used PuBe source (80 g pu) in the measurements [28,29]. On the other side, there is a remarkable shortage in the ratio of fast neutron fluxes at the energy range of 3 to 4 Mev which can be ascribed to the high attenuation at this definite energy (effective removal cross-section) unlike the 3-4 Mev for which a high flux of fast neutrons can be observed at the energy range of 4 to 5 Mev for all samples, indicating a decrease of the effective removal cross-section.…”
mentioning
confidence: 99%
“…According to the data obtained from Figures 8 and 9, it was observed that at a low energy range of 1.5 to 2.5 Mev, there is an evident increase in the flux intensity of fast neutrons at all spectra for all samples. These high neutron fluxes emanated from the fission of plutonium and the (n, 2n) reaction with Be nuclei are more significant due to the large size of the used PuBe source (80 g pu) in the measurements [28,29]. On the other side, there is a remarkable shortage in the ratio of fast neutron fluxes at the energy range of 3 to 4 Mev which can be ascribed to the high attenuation at this definite energy (effective removal cross-section) unlike the 3-4 Mev for which a high flux of fast neutrons can be observed at the energy range of 4 to 5 Mev for all samples, indicating a decrease of the effective removal cross-section.…”
mentioning
confidence: 99%